A reactive-sputter-deposited TiSiN nanocomposite coating for the protection of metallic bipolar plates in proton exchange membrane fuel cells. Issue 3 (15th February 2020) - Peng, Shuang; Xu, Jiang; Li, Zhengyang; Jiang, Shuyun; Munroe, Paul; Xie, Zong-Han; Lu, Hong
Abstract: To meet the needs of corrosion resistance and electrically conductivity for metallic bipolar plates that are employed in proton exchange membrane fuel cells (PEMFCs), a TiSiN nanocomposite coating was fabricated on to a Ti–6Al–4V substrate using reactive sputter-deposition through the double cathode glow discharge plasma technique. The microstructure of the TiSiN coating comprised nanocrystallite TiN grains embedded in an amorphous Si3 N4 matrix. Electrochemical measurements were employed to investigate the corrosion behavior of the TiSiN coating in the simulated operating environments of a PEMFC, specifically 0.5 M H2 SO4 solution containing different HF concentrations (namely 2, 4 and 6 ppm) at 70 °C pumped with H2 at the anode and air at the cathode. With increasing HF concentration, a higher corrosion current density and lower corrosion potential were observed from both the coating and the uncoated substrate, indicating that the addition of HF accelerated their corrosion rates under these conditions. Compared to the uncoated substrate, the TiSiN coating showed a markedly higher corrosion resistance at all HF concentrations. The passive film that formed on the TiSiN coating, with a resistance of the order of magnitude of ~10 7  Ω cm 2, displayed good electrochemical stability and was less affected by changes in HF concentration. For the TiSiN coating, the values of interfacial contact resistance (ICR) were 14.7 mΩ cm −2 and 18.3 mΩ cm −2, respectively, before and after 2.5 h potentiostatic polarization with 6 ppm HF under cathodic conditions under a compaction pressure of 140 N cm −2 . Both values are much lower than those for the bare substrate. Moreover, the TiSiN coating was shown to improve the hydrophobicity of Ti–6Al–4V that would help facilitate water management in the PEMFC operating environment. This coating, which exhibited excellent corrosion resistance, electro-conductivity and hydrophobicity, is therefore a promising material for protecting metallic bipolar plates from corrosive attack.